Experimental implementation of active force control on a vehicle suspension model - Muhaimin, Abdul Halim (Penerbit UTM, 2007)
A suspension system is typically an indispensable component of any automotive system since it can effectively isolate the impact, vibration and shock emanating from the surface terrain to the tyre and then to the passenger in the vehicle when the vehicle moves along the terrain. It thereby provides to a certain extent, riding comfort on the part of the passenger/s in the vehicle. Since the development of the vehicle suspension system, designers have been faced with the conflict of vehicle safety versus ride comfort. Originally, this trade-off was minimized by the single optimal adjustment of a passive spring and damper. In more recent years, the development of computer-controlled suspension dampers and actuators has increased the investigation of the vehicle safety versus ride comfort trade-off, and has led to the development of numerous active and semi active suspension control designs (Wilkinson, 1994).